The Portuguese version of the difficulties in emotion regulation scale and its relationship with psychopathological symptoms (Archives of Clinical Psychiatry, 2010)
BACKGROUND: Emotion dysregulation is a unifier dimension of several psychopathological symptoms thus an instrument that measures it is needed. OBJECTIVES: To adapt to Portuguese the Difficulties in Emotion Regulation Scale and study its psychometric qualities. A second goal was to explore the association between DERS dimensions and specific types of psychopathology symptoms. METHOD: The original measure was translated to Portuguese and completed by a sample of 324 individuals who also completed the Brief Symptom Inventory. RESULTS: The results show a very similar factor structure to the original measure: good testretest stability, very good internal consistency (Cronbach's α = ,93) and good external validity with BSI. The analysis performed with the subset of 115 individuals that composed the clinical sample showed that psychopathologic individuals present more difficulties in emotion regulation than normal individuals. Through the correlation analysis between the different DERS and BSI subscales, we found that the Strategies and Goals subscales present the highest level of association with all the psychopathological symptoms. DISCUSSION: This may suggest that these two dimensions are present in various psychological disorders and could, therefore, be included in psychological interventions focused on emotion regulation skills.